Prevalence of irritable bowel syndrome (IBS) and functional dyspepsia (FD) and their relationship with generalized anxiety disorder (GAD) among medical students in Karachi - Javed , Mahnoor; Yadav, Tularam; Shakil, Jibran; Zaidi, Syed Tafazzul Haider; Zehra, Mehwish (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the prevalence of inflammatory bowel syndrome and functional dyspepsia in medical students and their relationship with generalised anxiety disorder and other relevant factors. Method: The descriptive cross-sectional study was conducted in Karachi from August to November 2020 after approval from the ethics review board of Jinnah Sindh Medical University, and comprised students of either gender aged at least 18 years from different medical colleges in the city. Data was collected using validated tools Rome III criteria for inflammatory bowel syndrome and functional dyspepsia and Generalised Anxiety Disorder-7. Data was analysed using SPSS 26. Results: Of the 305 subjects, 185(60.70%) were male and 120(39.30%) were female. The overall mean age was 21.43±2.13 years. The prevalence of inflammatory bowel syndrome was 17(5.57%), while that of functional dyspepsia was 2(0.66%). Further, 122(40%) students had minimal anxiety, 112(36.72%) mild, 43(14.10%) moderate and 28(9.18%) had severe anxiety. There was no significant relationship of either inflammatory bowel syndrome or functional dyspepsia diagnosis with generalised anxiety disorder (p>0.05), but a significant relationship existed between inflammatory bowel syndrome diagnosis and generalised anxiety disorder score (p=0.041). Significant relationships were found between inflammatory bowel syndrome diagnosis and use of non-steroidal anti-inflammatory drugs. The relationship of generalised anxiety disorder diagnosis with gender and probiotic use was significant (p<0.05), and so was the relationship of generalised anxiety disorder score with gender and level of physical activity (p<0.05). Conclusion: Medical students with a higher generalised anxiety disorder score and those who used non-steroidal anti-inflammatory drugs frequently had a higher likelihood of developing inflammatory bowel syndrome. Key Words: Anxiety, Functional dyspepsia, Irritable bowel syndrome, Medical students.